Usefulness of CT colonography after incomplete or failed colonoscopy - Che Mohamed, Siti Kamariah; Abd. Aziz, Azian; Abdul Rashid, Mohd Amran; Md Ralib @ Md Raghib, Ahmad Razali; Mat Hassan, Mohd Zailani; Md Nor, Azmi; Mohd Yusof, Mubarak; Abdul Rahman, Zainun (2012)
OBJECTIVE To evaluate the clinical usefulness of CT Colonography after an incomplete or failed colonoscopy.